Novel Viral DNA Polymerases From Metagenomes Suggest Genomic Sources of Strand-Displacing Biochemical Phenotypes - Keown, Rachel A.; Dums, Jacob T.; Brumm, Phillip J.; MacDonald, Joyanne; Mead, David A.; Ferrell, Barbra D.; Moore, Ryan M.; Harrison, Amelia O.; Polson, Shawn W.; Wommack, K. Eric (Frontiers in Microbiology, 2022)
Viruses are the most abundant and diverse biological entities on the planet and constitute a significant proportion of the genetic diversity on Earth. Most of this diversity is not represented by isolated viral-host systems and has only been observed through sequencing of viral metagenomes (viromes) from environmental samples. Viromes provide snapshots of viral genetic potential, and a wealth of information on viral community ecology. These data also provide opportunities for exploring the biochemistry of novel viral enzymes. The in vitro biochemical characteristics of novel viral DNA polymerases was explored testing hypothesized differences in polymerase biochemistry according to protein sequence phylogeny. Forty-eight viral DNA Polymerase I (PolA) proteins from estuarine viromes, hot spring metagenomes, and reference viruses snapping a broad representation of currently known diversity were synthesized, expressed, and purified. Novel functionality was shown in multiple PolAs. Intriguingly, some of the estuarine viral polymerases demonstrated moderate to strong innate DNA strand displacement activity at high enzyme concentration. Strand-displacing polymerases have important technological applications where isothermal reactions are desirable. Bioinformatic investigation of genes neighboring these strand displacing polymerases found associations with SNF2 helicase-associated proteins. The specific function of SNF2 family enzymes is unknown for prokaryotes and viruses. In eukaryotes, SNF2 enzymes have chromatin remodeling functions but do not separate nucleic acid strands. This suggests that, for viruses carrying SNF2 helicase-associated proteins, the strand separation function may be fulfilled by the DNA polymerase itself. Biochemical data elucidated from this study expands our understanding of the biology and ecological behavior of unknown viruses. Moreover, given the numerous biotechnological applications of viral DNA polymerases, novel viral polymerases discovered within viromes may be a rich source of biological material for further advancements for in vitro DNA amplification.